A Prescription for Drug Formulary Evaluation: An Application of Price Indexes - Glazer, Jacob (2012)
Existing economic approaches to the design and evaluation of health insurance do not readily apply to coverage decisions in the multi-tiered drug formularies characterizing drug coverage in private health insurance and Medicare. This paper proposes a method for evaluating a change in the value of a formulary to covered members based on the economic theory of price indexes. A formulary is cast as a set of demand-side prices, and our measure approximates the compensation (positive or negative) that would need to be paid to consumers to accept the new set of prices. The measure also incorporates any effect of the formulary change on plan drug acquisition costs and “offset effects” on non-drug services covered by the plan. Data needed to calculate formulary value are known or can be forecast by a health plan. We illustrate the method with data from a move from a two- to a three-tier formulary.